(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This study tries to provide a comparative features of labor relations notions in some foreign nations. This study examines the legal laws and regulation of labor relationships, splitting states into 2 classifications. The initial incorporates Germany, Russia, France, and several other European nations. In the next - the USA, Australia, Great Britain, and other nations of the Anglo-Saxon legal systems. The comparative examination of various states’ legislation and formal-logical and functional methods are used to gratify the study’s objectives. The conclusion is made that the borrowing of the experience of the nations’ adhering to the Anglo-Saxon pattern is not acceptable for Russia because, in them, the contract of labor is demonstrated not as a means able to guarantee the workers’ rights but as a legal means to generate circumstances able to infringe on their benefits.